2017
DOI: 10.5194/cp-13-729-2017
|View full text |Cite
|
Sign up to set email alerts
|

Regional seesaw between the North Atlantic and Nordic Seas during the last glacial abrupt climate events

Abstract: Abstract. Dansgaard-Oeschger oscillations constitute one of the most enigmatic features of the last glacial cycle. Their cold atmospheric phases have been commonly associated with cold sea-surface temperatures and expansion of sea ice in the North Atlantic and adjacent seas. Here, based on dinocyst analyses from the 48-30 ka interval of four sediment cores from the northern Northeast Atlantic and southern Norwegian Sea, we provide direct and quantitative evidence of a regional paradoxical seesaw pattern: cold … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…They have equally denoted a similar atypical pattern over the whole Nordic Seas during the LGM (de Vernal et al, 2005), pointing out here again discrepancies between different proxies of sea-surface conditions (de Vernal et al, 2006) that were also reported in other multiproxy studies (e.g., Penaud et al, 2011;. In most cases, these discrepancies have been suggested to likely result from differences in ecological strategies between producers (e.g., de Vernal et al, 2006;Wary et al, 2015Wary et al, , 2017a. Dinoflagellates, as well as coccolithophorids or diatoms, are mostly restricted to the uppermost 50 meters of the water column (e.g.…”
Section: Past Sea Ice Cover In the Northern Hemispheresupporting
confidence: 73%
“…They have equally denoted a similar atypical pattern over the whole Nordic Seas during the LGM (de Vernal et al, 2005), pointing out here again discrepancies between different proxies of sea-surface conditions (de Vernal et al, 2006) that were also reported in other multiproxy studies (e.g., Penaud et al, 2011;. In most cases, these discrepancies have been suggested to likely result from differences in ecological strategies between producers (e.g., de Vernal et al, 2006;Wary et al, 2015Wary et al, , 2017a. Dinoflagellates, as well as coccolithophorids or diatoms, are mostly restricted to the uppermost 50 meters of the water column (e.g.…”
Section: Past Sea Ice Cover In the Northern Hemispheresupporting
confidence: 73%
“…2). Moreover, these age models have been validated by climate-independent tie points, such as tephra layers in core MD99-2284 43 , MD95-2010 44 and ENAM93-21 45 , or changes in the Earth’s magnetic field intensity in core MD99-2281 44 .…”
Section: Technical Validationmentioning
confidence: 99%